2017
DOI: 10.4103/jisppd.jisppd_265_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of effect of use of toothbrush with paste and munident on levels of Streptococcus mutans and gingival health in children: An in vivo study

Abstract: Munident (herbal) dentifrice has better gingival bleeding index compared to standard formulation of toothpaste. Hence, the practice of using herbal dentifrice should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
9
0
2
Order By: Relevance
“…It is reported that the rhizome part of Acorus calamus possesses numerous pharmacological activities such as CNS depressant, sedative, hypolipidemic, antimicrobial, anticonvulsant, anti-inflammatory, cryoprotective, immunosuppressive, anticancer, and antioxidant [19]. Recently an in vivo study was conducted on munident a herbal dentifrice having Acorus calamus as an ingredient was found to be effective in reducing gingival bleeding index score and Streptococcus mutans count [123]. The essential oil is extracted from the leaves of Acorus calamus using the steam distillation method.…”
Section: Acorus Calamus L (Sweet Flag or Vacha)mentioning
confidence: 99%
“…It is reported that the rhizome part of Acorus calamus possesses numerous pharmacological activities such as CNS depressant, sedative, hypolipidemic, antimicrobial, anticonvulsant, anti-inflammatory, cryoprotective, immunosuppressive, anticancer, and antioxidant [19]. Recently an in vivo study was conducted on munident a herbal dentifrice having Acorus calamus as an ingredient was found to be effective in reducing gingival bleeding index score and Streptococcus mutans count [123]. The essential oil is extracted from the leaves of Acorus calamus using the steam distillation method.…”
Section: Acorus Calamus L (Sweet Flag or Vacha)mentioning
confidence: 99%
“…Another study conducted by Shetty et al . [28] comparing the effect of commercially available tooth paste and herbal tooth paste (Munident) on Streptococcus mutans counts reported comparable findings in both the groups. However, toothbrush was used by participants in both the groups in the aforementioned study.…”
Section: Discussionmentioning
confidence: 86%
“…O controle do biofilme bacteriano é imprescindível para a manutenção da saúde bucal (Pithon et al, 2017;Ansari, Torabzadeh, Nabavi & Hassani, 2020 de cereja teria algum efeito na amilase salivar e no índice de 6, efeito esse comprovado no fim de sua pesquisa ao enfatizar a eficácia da composição de uma goma de mascar com extrato de cereja como método preventivo da cárie dentária. Ademais, os estudos de Shetty et al (2017) e Kamath et al (2019) enfatizaram também a importância da utilização de plantas medicinais, Research, Society andDevelopment, v. 9, n. 11, e67091110470, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10470 como Aloe vera e Melaleuca alternifolia, na composição de dentifrícios e colutórios para a redução do biofilme dentário e, consequentemente, redução do índice de S. mutans.…”
Section: Resultsunclassified